Pre-Extension Demonstration of Improved Durum Wheat Varieties with Their Associated Management Practices in Potential Growing Areas of Ethiopia - Mekuriaw, Truayinet (International Journal For Research In Agricultural And Food Science, 2022)
The objectives of this on-farm demonstration were to create awareness on the availability and importance of the new durum wheat varieties and to create wider demand pull by reaching large number of users over relatively wider geographical area. In addition to this the study aimed to enhance institutional and functional linkages with key players through joint actions and performances. Training and experience sharing events like field days were used to demonstrate the new improved varieties. For the on-farm demos seeds of the newly released varieties were provided to farmers at the rate of 120 kg/ha on a revolving seed loan basis. The plot size was 10 m x10 m at all locations. Training on agronomic practices (land preparation, sowing, weeding, harvesting and post-harvest handling) was given for farmers and experts by experienced researchers from respective departments. Farmer together with researchers and agricultural experts periodically evaluated the performance of each variety during group visit. Data were collected through field observation and direct measurements. A field day was organized at maturity stage at Akaki, Gimbich, Gelan, L.chiquala, Ambo and Welmera to visit the fields of demonstrated varieties and a total of 4181 participants (2676 male1505 female participants) attended the event. All the demonstrations were perform well at each site and great awareness has been created on the availability and importance of the new durum wheat varieties. In addition, good institutional linkages were established among the partners including district and zonal agriculture offices, seed producer companies and seed producing farmer cooperatives. This study recommend that, on-farmer and farmers’ training center (FTC) based demonstrations of improved new varieties would greatly enhance adoption and thereby production and productivity of durum wheat along with minimizing the risks of failures of the newly released varieties at on farm level. Working in collaboration with zonal and district agriculture offices and seed producers proved useful for the sustainability of new improved varieties in production.